Distribution of Colour Terms in Ostwald's Colour Space in Estonian, Finnish, Hungarian, Russian and English. - Uusküla, Mari (TRAMES: A Journal of the Humanities & Social Sciences, 2006)
This article presents the distribution of colour terms in Ostwald's colour space over five languages: Estonian, Finnish, Hungarian, Russian and English. All these languages have been argued to be stage VII languages in the terminology of Brent Berlin and Paul Kay, and thus to have 11 basic colour terms (except Russian, which probably has 12 basic colour terms). The data for all the languages represented in the present study is collected by using the field method presented by Ian Davies and Greville Corbett and is thus comparable. Sixty-five coloured tiles based on Ostwald's colour system are used as stimuli. Several colour terms in one language are found to be equivalent to colour terms in other languages, while in other cases one term in one language does not correspond to terms used in other languages. In addition, the best examples of colour or so-called focal points vary. As a result, it is claimed that the distribution of colour terms is not equal in related and non-related languages (there are either large or slight differences between colour naming depending on the concrete colour sample). It is therefore concluded that colour naming is a language-or even culture-specific quality. Reprinted by permission of the publisher.